Patient-derived esophageal adenocarcinoma organ chip: a physiologically relevant platform for functional precision oncology - Sanjima Pal; Elee Shimshoni; Salvador Flores Torres; Mingyang Kong; Kulsum Tai; Veena Sangwan; Nicholas Bertos; Swneke Donovan Bailey; Julie Bérubé; Donald E. Ingber; Lorenzo Ferri (Journal of Translational Medicine)
Abstract Background Esophageal adenocarcinoma (EAC) is the sixth most deadly cancer worldwide, with increasing incidence in North America. As no targeted therapy or immunotherapy has revolutionized the management of EAC, chemotherapy is the only standard of care. Most patients with EAC experience poor outcomes because of the inherent or acquired resistance to chemotherapy. Methods Adapting a patient-centered approach, we leveraged a microfluidic cell culture technology platform (Emulate), organoids derived from treatment-naive patient tumors or adjacent normal tissues, and patient-matched cancer-associated or normal fibroblasts respectively, to develop a novel, physiologically relevant, high-fidelity preclinical esophagus-on-a-chip model. H&E, immunofluorescence staining, live/dead assay, LDH assay, and ELISA-based detection of tumor biomarkers were used to assess treatment responses. Results Each patient-specific stroma-inclusive microfluidic esophageal adenocarcinoma on-a-chip (EAC chip) faithfully recreates the tumor-stroma interface while preserving the full diversity of two cell types (epithelia and fibroblasts), genetic landscapes and histological architecture of the source tumors. EAC chips also accurately predict the response to neoadjuvant chemotherapy (NACT) within a clinically useful timeframe (approx. 12 days). A docetaxel-based triplet chemotherapy regimen matched with the treatment of the source patient was successfully perfused through the interstitial space within this model. Therefore, EAC chips more accurately recapitulate inpatient pathological and objective responses than the corresponding static 3D-organoid-only cultures. Conclusions Overall, this model is an effective tool for predicting patients’ responses to chemotherapy and testing tumor- or stroma-targeted alternative therapies. Moreover, these high-fidelity, low-throughput EAC chips effectively complement high-throughput PDO culture-based drug testing and provide improved insights into drug efficacy before human studies. Graphical Abstract